EKSTRAKSI KOLAGEN DARI KULIT IKAN SELAR (Selaroides Leptolepis) DENGAN MENGGUNAKAN METODE LARUT ASAM DENGAN PENAMBAHAN ENZIM PEPSIN DAN PAPAIN - Ayu Dahliyanti; Nur Indah Shifani (JURNAL TEKNOLOGIA, 2022)
Pepsin soluble collagen (PSC) and papain soluble collagen (PaSC) were successfully extracted from the skin of Yellowstripe fish (Selaroides Leptolepis) through the combination of acid and enzymatic method. Collagen was obtained through a four-stage process which consisted of sample preparation, pretreatment, enzymatic extraction and salting out. Extraction was carried out for 12 hours and 24 hours by adding different doses of pepsin and papain enzymes. The highest yield of PSC and PaSC were 18.64% and 4.140% by mass. The as-prepared collagen were then analyzed for moisture content and ash content. Water content from PSC and PaSC were respectively 2.37% and 3.68% and the ash content was 15.87% and 35.89%, respectively. Fourier Transform Infrared (FTIR) analysis for both sample showed that the triple helix structure of collagen could be maintained even after the extraction process. From Differential Scanning Calorimetry (DSC) analysis, it was found that PSC and PaSC denaturation temperatures were of 64.05°C and 82.29°C.